THE LIFE, DEATH, AND AFTERLIFE OF GAMESPY: AN AUTOPSY OF A DEAD PLATFORM - Hewa, Nelanthi; Ross, Alexander (AoIR Selected Papers of Internet Research, 2026)
In the late 90s and early 2000s, GameSpy Network, was an inescapable presence of the early interactive web—either in the GameSpy Network—a collection of websites dedicated to covering popular game franchises (e.g Planet Quake, Planet Half-Life) or by working with game developers and publishers to provide multiplayer capabilities for hundreds of PC and console games. Even in instances when GameSpy did not provide the online infrastructure for a game, services like GameSpy Arcade gave users easy access—through monthly subscription fees or watching free ads—to multiplayer matchmaking, voice chat, and social features.Through its deliberate convergence of users, advertisers, publishers, and developers as multiple sides of a lucrative technology and content business, we see an early instance of a “multisided market” (Nieborg & Poell, 2018) that is a distinguishing feature of today’s digital platforms and their ecosystems. GameSpy might now be a “dead platform” (McCammon & Lingel, 2022) but in its death we find crucial insights about the past and future of digital platforms, and the undervalued labour necessary to support them. We situate our study at the intersections of journalism studies, platform studies, and game studies to examine GameSpy as an early instance of platformization (Helmond, 2015), digital journalistic labour (Cohen, 2015), and what David Nieborg and Maxwell Foxman (2023) call the “mainstreaming of games.” Though GameSpy predates the intense platformization that characterizes contemporary digital journalism, the enmeshment of journalistic editorial work with commercial advertising and player connectivity function as early clues for how the industry would continue to develop.